Salivary cortisol, heart rate, electrodermal activity and subjective stress responses to the Mannheim Multicomponent Stress Test (MMST) - Reinhardt, Tatyana; Schmahl, Christian; Bohus, Martin (Psychiatry research, 2012)
The availability of effective laboratory paradigms for inducing psychological stress is an important requirement for experimental stress research. Reliable protocols are scarce, usually laborious and manpower-intensive. In order to develop an economical, easily applicable standardized stress protocol, we have recently tailored the Mannheim Multicomponent Stress Test (MMST). This test has been shown to induce relatively high stress responses without focusing on social-evaluative components. In this study we evaluated changes in electrodermal activity and salivary cortisol in response to the MMST. The MMST simultaneously combines cognitive (mental arithmetic), emotional (affective pictures), acoustic (white noise) and motivational stressors (loss of money). This study comprised two independent experiments. For experiment 1, 80 female subjects were recruited; 30 subjects (15 females) participated in experiment 2. Significant changes in electrodermal activity and salivary cortisol levels in response to MMST exposure were found. Subjective stress and heart rate responses were significantly increased in both experiments. These results indicate that the MMST is an economical stress paradigm which is also applicable in larger cohorts or multicenter studies for investigating stress reactions. As social-evaluative threat is not the main stress component of the MMST, this procedure represents a useful and complementary alternative to other established stress protocols.